The innovation of shelf-reading supervision by using QR code technology in the UPM library. - Mohamed Fauzi, Mohamad Jefri; Zulkifli, Khairul Anwar; Adnan, Roni Iskandar; Syed, Shamila; Abu Seman @ Talib, Haslina (Faculty of Information Management, Universiti Teknologi MARA Cawangan Kedah, 2019)
Perpustakaan Sultan Abdul Samad (PSAS) has more than half a million of library collections which most of them are books. These books must be shelved systematically and arranged according to library’s objective which is “99 percent of the library materials are properly arranged and managed by the Customer Services Division.” Currently, there are 11 senior staff supervise 20 staff in managing book shelving by using printed form. The supervisor will then transfer the collected data to an Excel Spreadsheet individually, and finally compiled as an overall monthly report to be submitted to the head of department. This process involves 14 steps; lots of paper especially for the printed forms and several reports. Due to this, the objective of this project is to reduce cost, time and eliminate waste along the processes which might affect the departmental performance. New method was developed to monitor the output of shelf reading monitoring processes. Staff in charge is required to scan the QR Code on the shelf by using a smartphone to access the online form in the Google Drive. Data will be keyed-in while doing the shelf reading. This data will be stored in the Team Drive automatically to facilitate the supervisor for the daily monitoring. The outcomes of this project can be measured in four aspects. Firstly, paper and printing cost can be eliminated. Secondly, the work process and waiting time can be reduced by more than 50 percent. Thirdly, the monitoring of the process can be done in a real-time and finally the fourth aspect, report can be easily generated and shared. In conclusion, this project would enhance the performance of monitoring of the work process efficiently.